Isyarat Sentuhan Antena Semut (Dolichoderus Sp) Pada Tubuh Aphid (Aphis Sp) Untuk Memperoleh Embun Madu - Yayan Sunjaya; Harry Buana; Mimi Halimah (Fakultas Biologi | Universitas Jenderal Soedirman, 2009)
Ant, Dolichoderus sp, interact mutually with aphid (Aphis sp). The ants specifically communicate with the aphid by means of antennal sign. A hungry ant will approach an aphid and touch it dorsal part using ant antennae; in respond to this, will expel honey dew. To further study the pattern of communication between the ant and the aphid, their movement was recorded using Handycam JVC GR-SXM 300 AC. The records were processed using Adobe Premier Pro 1.5. The results showed that the ant antennae moved in a specific pattern which could be classified into 4 main steps. The first step consisted of 8 movements which formed 2 movement patterns. The second step consisted of 3 main repeated movements. The third step consisted of 3 main repeated movements. The fourth step consisted of 6 main movements which were repeated several times before the final movement. Such pattern of antennae movement was recognized by the aphid as tactile signal of ant identity.